Le Cahier Noir de Zinaida Gyppius - Rousseva, Zlatina (Belgium : Nicole Deschreider, 1997)
This is the Russian revolution, as seen and retold on a day-by-day basis by one of Russia's most interesting poets, Zinaida Gyppius. A woman of extraordinary talent, with a sharp, analytical mind, who was called "the witch" due to her acid tongue, she recorded all of the events in her diary, as a person felt and lived through them "from the inside." Her diaries provide a key to many of the events that would prove fatal for Russia, rerouting the course of European and world history. Having left Russia in 1900, she "buried" her diaries by turning them over to the Petersburg library under a false name. These diaries, discovered 80 years later and set to a timeline of the events of that era, form the basis of this film.
Duration: 01:30:00
Keywords: Documentary films